Implementasi Metode WebQual 4.0 untuk Analisis Kualitas Website Universitas Boyolali - Ari Wahyono; Wisnu Sanjaya (Universitas Boyolali, 2023)
As a higher education institution, Universitas Boyolali (UBY) has an official website with the address https://uby.ac.id. The main website conveys information to the academic community and the public. Website quality measurement is used as a basis for making improvements, so that website performance and quality are better. One of the methods for website measurement is using the WebQual 4.0 method. WebQual 4.0 Method measures a website's quality and focuses on three main dimensions: usability, information quality, and interaction service quality. This study aims to use the Webqual 4.0 method to measure quality with the website research object owned by Boyolali University, namely https://uby.ac.id. The study used 174 respondents using the non-probability incidental sample method for students, teaching staff, and lecturers at Boyolali University who had visited or accessed the website. The analysis results show that the Usability Dimension gets a percentage value of 78.62%, the Information Quality dimension is 78.22%, and service interaction is 77.75%. These results indicate that a percentage of respondents stated that they were satisfied with the quality of the UBY website.